(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study to focus on customers’ satisfaction of e-banking services in public sectors banks in Kancheepuram district, presently the modern banking sector has been providing enormous services rendered to various customer amongst services, the customer would get empowered due to a wide choice of services available on the net at a competitive cost. Thus, Internet banking presents a convenient and timesaving service for customers compared to traditional banking. Service is available on the web for twenty-four hours a day, seven days a week, and anywhere they need. For bankers, online banking presents more opportunity to provide customized services and appropriate supply and demand than traditional services. The aim of this research study will have retentions of their customer and attract new modern customers. Hence the banker will bring online banking services and remedy for all the grievances of banking customers.